Responsiveness of quantitative sensory testing-derived sensory phenotype to disease-modifying intervention in patients with entrapment neuropathy: a longitudinal study. Issue 12 (22nd December 2021) - Kennedy, Donna L.; Vollert, Jan; Ridout, Deborah; Alexander, Caroline M.; Rice, Andrew S.C.
Abstract : Quantitative sensory testing-derived sensory phenotype is responsive, identifying clinically important change in somatosensory function in patients undergoing disease-modifying intervention for entrapment neuropathy. Abstract: The German Research Network on Neuropathic Pain (DFNS) quantitative sensory testing (QST) method for sensory phenotyping is used to stratify patients by mechanism-associated sensory phenotype, theorised to be predictive of intervention efficacy. We hypothesised that change in pain and sensory dysfunction would relate to change in sensory phenotype. We investigated the responsiveness of sensory phenotype to surgery in patients with an entrapment neuropathy. With ethical approval and consent, this observational study recruited patients with neurophysiologically confirmed carpal tunnel syndrome. Symptom and pain severity parameters and DFNS QST were evaluated before and after carpal tunnel surgery. Surgical outcome was evaluated by patient-rated change. Symptom severity score of the Boston Carpal Tunnel Questionnaire and associated pain and paraesthesia subgroups were comparators for clinically relevant change. Quantitative sensory testing results (n = 76) were compared with healthy controls (n = 54). At 6 months postsurgery, 92% participants reported a good surgical outcome and large decrease in pain and symptom severity ( P < 0.001). Change in QST parameters occurred for thermal detection, thermal pain, and mechanical detection thresholds with a moderate to large effect size. Change in mechanical pain measures was not statistically significant. Change occurred in sensory phenotype postsurgery ( P < 0.001); sensory phenotype was associated with symptom subgroup ( P = 0.03) and patient-rated surgical outcome ( P = 0.02). Quantitative sensory testing-derived sensory phenotype is sensitive to clinically important change. In an entrapment neuropathy model, sensory phenotype was associated with patient-reported symptoms and demonstrated statistically significant, clinically relevant change after disease-modifying intervention. Sensory phenotype was independent of disease severity and may reflect underlying neuropathophysiology.